Management of ADHD in Prisoners—Evidence Gaps and Reasons for Caution - Tully, John (Frontiers in Psychiatry, 2022)
A focus on adult ADHD has emerged in the last decade, with concerns that the condition is under-recognised and undertreated in prisoners. Calls for a shift in emphasis are likely driven in part by exasperation with lack of effective treatments for other disorders, especially ASPD, which is exceptionally common in prisoners. There is much enthusiasm for developing assessment and treatment pathways and optimism that this will result in significant improvements in outcomes. To date, however, evidence to support this is very limited. Particular concerns surround disproprortionate demand on resources, lack of evidence for mechanistic links between ADHD and antisocial behaviour, and insufficient risk: benefit considerations in prescribing guidelines. This article discusses specific gaps in evidence that must be bridged in order to justify increased allocation of resources to assessment and treatment of ADHD in prisoners, and to support a basis for prescribing medication as a frist-line treatment. In the interim, the importance of ADHD in prisoners should be considered as under review and ADHD management incorporated into a proprotionate approach to prison mental healthcare.